Midline anterior neck inclusion cyst. - Alfaro-Sepúlveda, D.; González-Fuentes, C.G. (European Journal of Pediatric Dermatology, 2020)
Recently described by Walsh et Al. (2) midline anterior neck inclusion cyst is a superficial developmental anomaly of the midline lower neck; it is clinically reminiscent of a giant milium and pathologically of an infundibular follicular cyst. To date, there are 8 cases reported. Thanks to its superficial location and clinical appearance MANIC can be differentiated from thyroglossal duct cyst, which present as a subcutaneous mass moving upwards with swallowing, from midline cervical cleft with its characteristic linear atrophy and from bronchogenic cyst characterized by a subcutaneous nodule (1). The diagnosis is clinical; however, ultrasound can help to differentiate other entities. Although spontaneous regression may sometimes occur (2), surgical removal is usually performed.